Moringa oleifera mitigates oxytetracycline stress in Oreochromis niloticus. (10th December 2021) - Sherif, Ahmed H.; Prince, Abdelbary; Adel Seida, Ahmed; Saad Sharaf, Mahmoud; Eldessouki, Elsayed A.; Harfoush, Mohammed A.
Abstract: Antibiotics serve as the cornerstone of the treatment of bacterial diseases in the aquaculture sector. In this study, 210 Nile tilapias ( Oreochromis niloticus ) weighing approximately 60 ± 2.5 g b.w. were randomly divided into seven treatments (T1–7). The fish were experimentally infected with Aeromonas hydrophila and then treated with oxytetracycline (OTC) after the appearance of clinical symptoms. The fish were fed Moringa oleifera diet alone or M .  oleifera diet before OTC treatment to alleviate the effects of OTC treatment. The effects of OTC treatment and M .  oleifera were assessed by measuring the gene expressions of cytokines (interleukin [IL]‐1β, IL‐6, tumour necrosis factor‐α, IL‐10 and heat shock protein‐70), antioxidant enzymes (catalase, superoxide dismutase, lipid peroxidase and total antioxidant capacity) and liver enzymes (aspartate aminotransaminase, alanine aminotransaminase and alkaline phosphatase). Although OTC treatment protected fish from A .  hydrophila, leading to a decreased mortality rate (49.96%), it exerted deleterious effects on their immune and oxidative statuses. Thus, we recommend that M .  oleifera be included in the feed of O .  niloticus, especially those exposed to bacterial infection.